2022
DOI: 10.3390/biology11091372
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Adhesion to Skin Keratinocytes and Underlying Mechanisms

Abstract: The effects of probiotics on the skin are not yet well understood. Their topical application and benefits derived thereafter have recently been investigated. Improvements in different skin disorders such as atopic dermatitis, acne, eczema, and psoriasis after their use have, however, been reported. One of the mechanisms through which such benefits are documented is by inhibiting colonization by skin pathogens. Bacterial adhesion is the first step for colonization to occur; therefore, to avoid pathogenic coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Probiotics usage including lactobacillus could ameliorate skin conditions suggesting them as a potential co-adjuvant for the treatment of skin infections (15). Previous studies have suggested that probiotic strain extension in the vaginal area could be able to prevent and reduction of HPV infections or expansion the HPV-induced warts (16).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics usage including lactobacillus could ameliorate skin conditions suggesting them as a potential co-adjuvant for the treatment of skin infections (15). Previous studies have suggested that probiotic strain extension in the vaginal area could be able to prevent and reduction of HPV infections or expansion the HPV-induced warts (16).…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans ) [ 57 ]. DSM 20021 strain can reduce the adhesion of pathogenic bacteria [ 58 ]. All these strains contain bacteriocin-related genes and have the ability to inhibit the growth of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This process disrupted by an imbalanced skin microbiota. Ming et al and Lizardo et al foun probiotics of genus Lactobacillus protected the wound from pathogenic bacteria a anti-inflammatory capabilities [4,12]. In another study, Staphylococcus epidermidis, commensal bacterium, was shown to produce anti-inflammatory lipoteichoic ac The use of probiotics in wound healing is poorly described, especially in animals.…”
Section: Discussionmentioning
confidence: 99%